T-MOOC, cognitive load and performance: analysis of an experience - Cabero-Almenara, Julio; Barroso-Osuna, Julio; Gutiérrez-Castillo, Juan Jesús; Palacios Rodríguez, Antonio (Revista Electrónica Interuniversitaria de Formación del Profesorado, 2023)
The study of cognitive load allows us to investigate the effectiveness of any training proposal mediated by technology. This paper presents the results of the implementation of a t-MOOC produced following the DigCompEdu Framework of the European Union. The participants are a group of students (n= 148) from the first year of the Pedagogy Degree (University of Seville) of the Educational Technology subject. To do this, the level of cognitive load invested in the interaction with the t-MOOC is analyzed using a validated scale. Secondly, the relationship between the invested cognitive load and the performance achieved in the experience carried out with the contents of two competence areas is studied. After the different analyzes applied, the study concludes that the t-MOOC produced is considered appropriate for the development of digital skills in students. In addition, although the correlations between cognitive load and academic performance were not very high, both are related. In this sense, the potential of training proposals focused on the development of digital skills and the benefits of applying cognitive load studies are discussed.